COVID‐19 vaccines and risks of hematological abnormalities: Nested case–control and self‐controlled case series study. Issue 4 (9th February 2022) - Sing, Chor‐Wing; Tang, Casey Tze Lam; Chui, Celine Sze Ling; Fan, Min; Lai, Francisco Tsz Tsun; Li, Xue; Wan, Eric Yuk Fai; Wong, Carlos King Ho; Chan, Esther Wai Yin; Hung, Ivan Fan Ngai; Leung, Anskar Yu‐Hung; Cheung, Ching‐Lung; et al.
Abstract: Several studies reported hematological abnormalities after vaccination against the coronavirus disease 2019 (COVID‐19). We evaluated the association between COVID‐19 vaccines (CoronaVac and BNT162b2) and hematological abnormalities. We conducted nested case–control and self‐controlled case series analyses using the data from the Hong Kong Hospital Authority and the Department of Health, HKSAR. Outcomes of interest were thrombocytopenia, leukopenia, and neutropenia. Adjusted odds ratios (aORs), incidence rate ratios (IRRs), and 95% confidence intervals (CIs) were estimated using conditional logistic regression. In total, 1 643 419 people received COVID‐19 vaccination (738 609 CoronaVac; 904 810 BNT162b2). We identified 457 and 422 cases after CoronaVac and BNT162b2 vaccination, respectively. For CoronaVac, the incidence of thrombocytopenia, leukopenia, and neutropenia was 2.51, 1.08, and 0.15 per 10 000 doses. For BNT162b2, the corresponding incidence was 1.39, 1.17, and 0.26 per 10 000 doses. The incidence per 10 000 COVID‐19 cases were 1254, 2341, and 884, respectively. We only observed an increased risk of leukopenia following the second dose of BNT162b2 (aOR 1.58, 95% CI 1.24–2.02; day 0–14, IRR 2.21; 95% CI 1.59–3.08). There was no increased risk of any hematological abnormalities after CoronaVac vaccination. We observed an increased risk of leukopenia shortly after the second dose of BNT162b2. However, the incidence was much lower than the incidence following severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infections. There was no association between CoronaVac and hematological abnormalities. The benefits of vaccination against COVID‐19 still outweigh the risk of hematological abnormalities.